2012
DOI: 10.1093/nar/gks399
|View full text |Cite
|
Sign up to set email alerts
|

The histone demethylase Kdm3a is essential to progression through differentiation

Abstract: Histone demethylation has important roles in regulating gene expression and forms part of the epigenetic memory system that regulates cell fate and identity by still poorly understood mechanisms. Here, we examined the role of histone demethylase Kdm3a during cell differentiation, showing that Kdm3a is essential for differentiation into parietal endoderm-like (PE) cells in the F9 mouse embryonal carcinoma model. We identified a number of target genes regulated by Kdm3a during endoderm differentiation; among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Knock down of the Kdm3a product, Jmjd1a, was shown to affect a large number of downstream targets; global mRNA expression showed that 125 genes were up‐regulated and 100 genes were down‐regulated [Loh et al, ]. Kdm3a has essential role in early embryonic differentiation with crucial regulatory and inductor function for a number of specific downstream genes [Herzog et al, ]. Complete knockout of Jmjd1a causes adult onset obesity, hyperlipidemia, and other signs of metabolic syndrome [Tateishi et al, ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knock down of the Kdm3a product, Jmjd1a, was shown to affect a large number of downstream targets; global mRNA expression showed that 125 genes were up‐regulated and 100 genes were down‐regulated [Loh et al, ]. Kdm3a has essential role in early embryonic differentiation with crucial regulatory and inductor function for a number of specific downstream genes [Herzog et al, ]. Complete knockout of Jmjd1a causes adult onset obesity, hyperlipidemia, and other signs of metabolic syndrome [Tateishi et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Complete knockout of Jmjd1a causes adult onset obesity, hyperlipidemia, and other signs of metabolic syndrome [Tateishi et al, ]. We are unaware of pathogenic KDM3A variants for ID, although there are reports of somatic mutations implicated in cancer [Herzog et al, ]. ClinGen reported a ∼400 kb loss variant (nssv577707) including KDM3A and two adjacent genes in a patient with “developmental delay and additional significant developmental and morphological phenotypes.” A DECIPHER loss CNV, two gains in DECIPHER and two gains in ClinGen completely include this gene; however, all are several Mb in size.…”
Section: Resultsmentioning
confidence: 99%
“…This regulation is unexpected of a direct Jmjd1a/G9a epigenetic function and may instead be due to changes in the H3K9 methylation status or expression of antiangiogenic genes that produce microenvironments conducive or detrimental to the maintenance of stem celllike populations, respectively. The significant effects of Jmjd1a/ G9a with the onset of hypoxia during tumor formation, in contrast to the lack of pluripotency defects in ES cells, highlight the effect of hypoxia on the expression of pluripotency genes and further suggest that Jmjd1a/G9a may become important only upon exit from self-renewal and the subsequent onset of differentiation, rather than at ES cell self-renewal stages (48), affecting the status of stem cell-like populations needed for tumor growth.…”
Section: Discussionmentioning
confidence: 98%
“…KDM3A also has a role in maintaining pluripotency in ESCs by demethylation of H3K9 leading to expression of pluripotency factors. The same study found that KDM4C also regulates maintenance of pluripotency via H3K9 demethylation [111]. KDM4A and KDM4B are essential to Drosophila development and mediate ecdysteriod hormone signaling leading to transcriptional activation of ecdysone response genes [112].…”
Section: Jmjc-kdms and Developmentmentioning
confidence: 91%